Advanced Topics in Environmental Sociology - Dunlap, Riley (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Course Objectives1. Provide you will a good sense of the large, multidisciplinary body of literature on environmental attitudes, beliefs, values and other cognitions2. Help you make sense of public opinion polls on environmental issues3. Familiarize you with the key conceptual and methodological issues that will help you to make sense of the vast amount of relevant literature on EABV4. Familiarize you with the latest measurement techniques employed in the field5. Provide you with the tools you need to critically evaluate existing and future studies studies of EABV6. Provide you with the tools you need to design your own survey dealing with Environmental issues